THE TRANSLATION OF METAPHORS IN HARRY POTTER AND THE CHAMBER OF SECRETS FROM ENGLISH TO INDONESIAN - Khairuddin Khairuddin (University of Kuningan, 2015)
Abstract: Translation is undoubtedly an important but at the same time difficult work. Metaphors are among the potential areas of translation problem. This study aimed at describing how metaphors in the novel Harry Potter and the Chamber of Secrets are translated from English to Indonesian, and evaluating the appropriateness of the translation results. Findings showed certain strategies were applicable and determinant to the appropriateness of the English metaphor translation to Indonesian: adoption or reproduction, adaptation or replacement with Indonesian metaphors, conversion to simile, adoption plus sense, conversion to sense, and deletion. Metaphor translation appropriateness shall be arrived if it qualifies referential and contextual accuracy. Missing one or either two of the accuracy kinds may result in less and inappropriate metaphor translation respectively.Â Keywords: translation, metaphorical expression, translation appropriateness, metaphor translation strategies.